Development of Integrity Zone Towards Corruption-Free (WBK)/Clean Bureaucracy (WBBM) at Work Unit Law Faculty UNNES - Aprila Niravita; Tri Andari Dahlan; Rahayu Fery Anitasari; Andry Setiawan; Ayup Suran Ningsih (Universitas Negeri Semarang, 2023)
Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform Number 25 of 2020, which underlines the 2020-2024 Bureaucratic Reform Road Map, guides the government's efforts to realize world-class government. The goal of bureaucratic reform is to achieve three main conditions: a clean and accountable bureaucracy, a capable bureaucracy, and optimal public services. The Faculty of Law at Universitas Negeri Semarang(UNNES) is one of the units committed to achieving high standards of integrity. This requires structuring good governance, optimal public services, and high integrity for all human resources at the Faculty of Law. Therefore, this study aims to examine the readiness of the Faculty of Law in building Integrity Zones, especially in achieving Free from Corruption Areas (WBK) and Clean and Serving Bureaucratic Areas (WBBM). This research uses doctrinal or normative research methods with concept and case approaches. Legal materials are collected through the study of documents and presented systematically following legal issues and research problems. Then it is analyzed qualitatively juridically. The results of the study identify strategies used by the Faculty of Law to build Integrity Zones towards WBK and WBBM. In addition, this study also identifies the strengths and weaknesses of the Faculty of Law in achieving these goals. This in-depth understanding of the readiness of the Faculty of Law in bureaucratic reform is expected to guide improving bureaucratic performance and integrity at the faculty level.